Controllability of a cylindrical shell in a fluid and in an acoustic field. Issue 10 (27th July 2021) - Lee, Doo-Sung
ABSTRACT: In this paper, we show that a thin cylindrical shell which is surrounded by an inviscid fluid or an acoustic system is controllable. A cylindrical shell is exactly controllable by a single control at one end. The analysis shows that the same results can be obtained when it is submerged in an ideal fluid or in an acoustic field.